Strengthening Community-Based NCD Prevention through Service Quality and Availability: Lessons from Banjarmasin City - Adi Nugroho; Rosihan Adhani; Acim Heri Iswanto; Muhammad Abdan Shadiqi; Herawati Herawati; Meitria Syahadatina Noor; M. Ramadhan; Ayu Riana Sari Azwari (Media Kesehatan Masyarakat Indonesia, 2025)
The main cause of death both globally and nationally is Non-Communicable Diseases (NCDs). Integrated Non-Communicable Disease Posts (INCDs Posts) play a crucial role in early detection and control of NCD risk factors at the community acceptance of INCDs Posts services. This study aims to analyse the influence of accessibility, availability, and services on community acceptance of INCD Posts in Banjarmasin City. A cross-sectional design was used, with data analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) on 654 respondents. The variables analysed included accessibility, availability, quality, and community acceptance of INCDs Post services. The results of the study indicate that service quality and availability have a positive and significant impact on community acceptance, while accessibility does not have a significant direct impact. Service quality also acts as a mediator between accessibility and acceptance, as well as between accessibility and availability. Overall, service quality and availability are the dominant factors influencing community acceptance. These findings recommend that health policies should shift from an access focused model to a quality-oriented framework. In particular, policymakers should prioritise capacity building and resource reliability over further infrastructure expansion in order to build public trust and ensure the long-term sustainability of community based non-communicable disease prevention programmes.